Postoperative inflammation and insulin resistance in relation to body composition, adiposity and carbohydrate treatment: a randomised controlled study - Tewari, Nilanjana; Awad, Sherif; Duška, František; Williams, Julian P.; Bennett, Andrew; MacDonald, Ian A.; Lobo, Dileep N. (Elsevier, 2018)
Background and Aims: The aims of this study were to identify whether differences in distribution of adipose tissue and skeletal muscle in obese and non-obese individuals contribute to the magnitude of the postoperative inflammatory response and insulin resistance, with and without preoperative treatment with carbohydrate drinks. Methods: Thirty-two adults (16 obese/16 non-obese) undergoing elective major open abdominal surgery participated in this 22 factorial, randomised, double-blind, placebo-controlled study. Participants received Nutricia preOp® or placebo (800 ml on the night before surgery/400 ml 2-3 h preoperatively) after stratifying for obesity. Insulin sensitivity was measured using the hyperinsulinaemic-euglycaemic clamp pre- and postoperatively. Vastus lateralis, omental and subcutaneous fat biopsies were taken pre- and postoperatively and analysed after RNA extraction. The primary endpoint was within subject differences in insulin sensitivity. Results: Major abdominal surgery was associated with a 42% reduction in insulin sensitivity from mean(SD) M value of 37.3(11.8) μmol kg-1 fat free mass (FFM) to 21.7(7.4) μmol kg-1 67 FFM, but this was not influenced by obesity or preoperative carbohydrate treatment. Activation of the triggering receptor expressed on myeloid cells (TREM1) pathway was seen in response to surgery in omental fat samples. In postoperative muscle samples, gene expression differences indicated activation of the peroxisome proliferator-activated receptor (PPAR-α)/retinoid X-receptor (RXR-α) pathway in obese but not in non-obese participants. There were no significant changes in gene expression pathways associated with carbohydrate treatment. Conclusion: The reduction in insulin sensitivity associated with major abdominal surgery was confirmed but there were no differences associated with preoperative carbohydrates or obesity.